Are sample size and sample preparation for mycotoxin quantitation in grain products getting trivialized?. (December 2021) - Kumphanda, Joseph; Matumba, Limbikani; Monjerezi, Maurice; Whitaker, Thomas B.; De Saeger, Sarah; Makun, Hussaini Anthony
Abstract: Sampling and sample preparation (grinding and subsampling) are largest sources of variability that negate precision and accuracy of mycotoxin quantitation, particularly in grains. In general, halving sample or sub-sample (e.g., ground test portion) size doubles variance. Therefore, this paper reports on trends in sample and test portion masses used for the quantification of mycotoxin in maize between 1991 and 2020 by reviewing articles on mycotoxin quantitation in maize (grain and flour) published during this period. About 50% of the articles did not explicitly state the sample mass that was ground. Sample and test portion masses show a significant (p < 0.05) decline over the study period. In addition, over two-thirds of the articles did not specify the type of grinder and sieve sizes used in their analysis. Therefore, our findings suggest that standardized sampling plans with emphasis on laboratory sample size and sample preparation methods for maize are increasingly being overlooked during mycotoxin quantitation and increasing the uncertainty associated with estimating the true mycotoxin concentration in grain lots. Graphical abstract: Image 1